Postretrieval Microinjection of Baclofen Into the Agranular Insular Cortex Inhibits Morphine-Induced CPP by Disrupting Reconsolidation - Sun, Kuisheng; Mu, Qingchun; Chang, Haigang; Zhang, Chun; Wang, Yehua; Rong, Shikuo; Liu, Shenhai; Zuo, Di; He, Zhenquan; Wan, Ding; Yang, Hua; Wang, Feng; et al. (Frontiers in Pharmacology, 2020)
Environmental cues associated with drug abuse are powerful mediators of drug craving and relapse in substance-abuse disorders. Consequently, attenuating the strength of cue-drug memories could reduce the number of factors that cause drug craving and relapse. Interestingly, impairing cue-drug memory reconsolidation is a generally accepted strategy aimed at reducing the intensity of cues that trigger drug-seeking and drug-taking behaviors. In addition, the agranular insular cortex (AI) is an important component of the neural circuits underlying drug-related memory reconsolidation. GABAB receptors (GABABRs) are potential targets for the treatment of addiction, and baclofen (BLF) is the only prototypical GABAB agonist available for application in clinical addiction treatment. Furthermore, ΔFosB is considered a biomarker for the evaluation of potential therapeutic interventions for addiction. Here, we used the morphine-induced conditioned place preference (CPP) paradigm to investigate whether postretrieval microinjections of BLF into the AI could affect reconsolidation of drug-reward memory, reinstatement of CPP, and the level of ΔFosB in mice. Our results showed that BLF infused into the AI immediately following morphine CPP memory retrieval, but not 6 h postretrieval or following nonretrieval, could eliminate the expression of a morphine CPP memory. This effect persisted in a morphine-priming–induced reinstatement test, suggesting that BLF in the AI was capable of preventing the reconsolidation of the morphine CPP memory. Our results also showed that the elimination of morphine CPP memory was associated with reduced morphine-associated ΔFosB expression in the longer term. Taken together, the results of our research provide evidence to support that GABABRs in the AI have an important role in drug-cue memory reconsolidation and further our understanding of the role of the AI in drug-related learning and memory.